Family planning service receipt during facility visits in Ethiopia: Evidence from the 2021–2022 service provision assessment survey - Melkamu Chafamo Joche; B. Muniswamy; B. Punyavathi (PLoS ONE, 2026)
Background Family planning is a central component of reproductive health and contributes to reductions in maternal and child mortality. While most evidence in Ethiopia is derived from household surveys, limited attention has been given to service delivery at the point of care. This study examines determinants of receipt of family planning services during facility visits using nationally sampled Service Provision Assessment (SPA) survey data. Methods A facility-based cross-sectional analysis was conducted using nationally implemented SPA survey data. The survey employed a stratified multistage sampling design, in which health facilities were selected within strata defined by region, managing authority, and facility type, followed by systematic sampling of clients within facilities for exit interviews. The study included 2,588 women aged 15–49 years who attended sampled facilities and completed client exit interviews. The outcome was receipt of any family planning service during the visit, defined as provision of counseling and/or a contraceptive method, reflecting service delivery at the point of care rather than contraceptive use. Multivariable logistic regression was used to assess associations between client characteristics, provider attributes, and facility-level factors. Exploratory interaction analyses were conducted but not retained in the final model due to instability and sparse data structures. Adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were reported, and statistical significance was defined at a two-sided p-value < 0.05. All analyses were conducted using R (version 4.5.3). Results Overall, 64.2% of clients received a family planning service during their visit. After adjustment, clients without prior contact with a provider had higher odds of receiving a service compared with those reporting prior contact (AOR = 2.25; 95% CI: 1.86–2.72; p < 0.001). Married women had lower odds of receiving a service than single women (AOR = 0.69; 95% CI: 0.49–0.98; p = 0.030). Substantial regional variation was observed, with lower odds in Amhara (AOR = 0.29; 95% CI: 0.17–0.49) and Addis Ababa (AOR = 0.41; 95% CI: 0.23–0.73), and higher odds in Benishangul-Gumuz, Gambella, and Dire Dawa. Other covariates were not statistically significant after adjustment, and observed associations should be interpreted as reflecting service delivery processes at the point of care rather than underlying contraceptive demand. Conclusions Family planning service receipt during facility visits in Ethiopia is associated with prior client–provider contact, marital status, and regional context. The persistence of regional differences after adjustment indicates that contextual factors related to health system performance and service delivery environments play a role in shaping service delivery during clinical encounters. The findings indicate heterogeneity in service delivery at the point of care, suggesting the need for context-specific strategies to improve the consistency and quality of family planning services within health facilities.